Concrete passions: Anscombe's material politics - McCarthy, Christine (Architectural History Aotearoa, 2011)
Edmund Anscombe (1874-1948) was an advocate of concrete as a building material, especially in relation to housing. This paper examines Anscombe's promotion of concrete, with specific reference to his patented OK blocks in the 1920s, a time when he is better known for his work on the University of Otago campus, the 1925 New Zealand and South Seas Exhibition, and his move from Dunedin to Wellington in 1928.